Marathon performance but not BMI affects post-marathon pro-inflammatory and cartilage biomarkers - Mundermann, Annegret; Geurts, Jeroen; Hugle, Thomas; Nickel, Thomas; Schmidt-Trucksass, Arno; Halle, Martin; Hanssen, Henner (Journal of Sports Sciences, 2017)
We tested the hypothesis that changes in serum cartilage oligomeric matrix protein (COMP), tumour necrosis factor α (TNF-α), interleukin-6 (IL-6) and high-sensitivity C-reactive protein (hsCRP) concentration after regular endurance training and running a marathon race depend on body mass index (BMI) and/or on marathon performance. Blood samples were collected from 45 runners of varying BMI and running experience before and after a 10-week marathon training programme and before, immediately and 24 h after a marathon race. Serum biomarker concentrations, BMI and marathon finishing time were measured. The mean (95% confidence interval (CI)) changes from before to immediately after the marathon were COMP: 4.09 U/L (3.39–4.79 U/L); TNF-α: −1.17 mg/L (−2.58 to 0.25 mg/L); IL-6: 12.0 pg/mL (11.4–12.5 pg/mL); and hsCRP: −0.08 pg/mL (−0.14 to −0.3 pg/mL). The mean (95% CI) changes from immediately after to 24 h after the marathon were COMP: 0.35 U/L (−0.88 to 1.57 U/L); TNF-α: −0.43 mg/L (−0.99 to 0.13 mg/L); IL-6: −9.9 pg/mL (−10.5 to −9.4 pg/mL); and hsCRP: 1.52 pg/mL (1.25–1.79 pg/mL). BMI did not affect changes in biomarker concentrations. Differences in marathon finishing time explained 32% of variability in changes in serum hsCRP and 28% of variability in changes in serum COMP during the 24 h recovery after the marathon race (P < 0.001). Slower marathon finishing time but not a higher BMI modulates increases in pro-inflammatory markers or cartilage markers following a marathon race.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Cartilage biomarkers; marathon running; obesity; pro-inflammatory markers; tissue metabolism